Relationship between childhood trauma and risk-taking and self-harm behaviors among Eswatini adolescents - Thobile Ntshalintshali; Mokoena Patronella Maepa (Acta Psychologica)
Background: There is a high number of child abuse and neglect cases globally that are associated with risk-taking and self-harm behaviors among adolescents in the Kingdom of Eswatini. Participants and setting: A sample of 470 adolescent boys and girls 16.57 years from selected high schools in Eswatini participated in the study. Methods: Childhood Trauma Questionnaire (CTQ) was used to assess childhood trauma and neglect. The Risk-taking and Self-harm Inventory for adolescents was utilized to measure adolescent risk-taking (RT) and self-harm (SH). A Pearson correlation coefficient and linear regression were used to test the association of childhood trauma with risk-taking and self-harm behaviors. Results: Results indicated an overall significant positive relationship between childhood trauma (emotional abuse (r(467) = 0.195, p < .001), physical abuse (r(470) = −0.245, p < .001), sexual abuse (r(469) = 0.205, p < .001), and risk-taking behavior and significant positive relationship between emotional abuse (r(288) = 0.347, p < .001), physical abuse (r(290) = 0.290, p < .001), sexual abuse (r(290) = 0.293, p < .001), and emotional neglect (r(290) = −0.193, p < .001), and physical neglect (r(290) = −0.121, p < .04) and self-harm behavior. Conclusions: A significant correlation was found between childhood trauma and risk-taking and self-harm behaviors. Emotional, physical, and sexual abuse correlated with risk-taking behavior while all aspects of childhood trauma correlated with self-harm behavior.